The Impact of working as a bus driver on women‘s health, workplace relationships and family functioning : the experiences of black female bus drivers in Tshwane, South Africa - Du Plessis, Irma (University of Pretoria, 2014)
Dissertation (MSocSci)--University of Pretoria, 2013.